2020
DOI: 10.12669/pjms.36.5.2403
|View full text |Cite
|
Sign up to set email alerts
|

The association among 14-3-3η protein, inflammation, bone remodeling and osteoporosis in patients with rheumatoid arthritis

Abstract: Objective: To evaluate the correlation among 14-3-3η protein, inflammation, bone remodeling and osteoporosis in patients with rheumatoid arthritis. Methods: In this cross-sectional study, the RA patients treated in our hospital were analyzed between January 2015 and November 2019. Bone mineral density was measured using dual energy X-ray absorptiometry, and at the beginning of the study, serum samples were collected and the level of 14-3-3η, TNF-α, and IL-6 was tested using the quantitative enzyme-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 11 publications
2
13
0
1
Order By: Relevance
“…46 14-3-3η predicts disease activity of RA and its duration, and when combined with other biomarkers such as anti-CCP and RF, its diagnostic ability improves. [25][26][27] This has also been consistent with previous studies. 47 14-3-3η is a predictor of bone remodelling and RA related osteoporosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…46 14-3-3η predicts disease activity of RA and its duration, and when combined with other biomarkers such as anti-CCP and RF, its diagnostic ability improves. [25][26][27] This has also been consistent with previous studies. 47 14-3-3η is a predictor of bone remodelling and RA related osteoporosis.…”
Section: Discussionsupporting
confidence: 93%
“…The level of 14-3-3η was highest in the osteoporosis group compared to the normal group (p<0.05). 25 Similarly, another study showed that 14-3-3η positively correlated with inflammation and disease risk as reported by Tu J et al 26 14-3-3η was significantly increased in RA patients, and ROC analysis indicated that it served as a potential predictive marker for RA risk. 26 14-3-3η distinguished patients with established RA (disease duration >2 years) compared to early RA patients ([?…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present study, a significant difference in the serum levels of 14-3-3η and IL _ 6 among RA-control, RA-osteopenia, and RA-osteoporosis groups was found being lowest in the RA-control group and highest in the RA-osteoporosis group. These findings were in agreement with the findings of a previous studies [22,28], and showed an inverse correlation with lumbar and femoral BMD among RA patients [22]. Zeng et al [29] found that serum 14-3-3η protein was significantly higher among RA cases than controls and the regression analysis identified 14-3-3η as an independent risk factor for RA-related osteoporosis.…”
Section: Discussionsupporting
confidence: 91%
“…В опытах in vitro было показано, что стимуляция моноцитов 14-3-3η сопровождалась индукцией синтеза ИЛ-1β, ИЛ-6, ММП-9 и RANKL (receptor activator of nuclear factor kappa-B ligand) [67]. Отмечена отрицательная корреляция между увеличением концентрации 14-3-3η и показателями минеральной плотности костей (МПК) по данным рентгеновской денситометрии, независимо от уровня СРБ, IgM РФ и АЦЦП [68][69][70]. Установлено, что увеличение концентрации 14-3-3η у пациентов с РА может быть предиктором хорошего «ответа» на терапию ингибитором ИЛ-6 (тоцилизумаб) и ингибиторами ФНО-α [66,71].…”
Section: -3-3ηunclassified